Real‐life experience in the treatment of solar urticaria: retrospective cohort study. (1st July 2019) - Snast, I.; Lapidoth, M.; Uvaidov, V.; Enk, C. D.; Mazor, S.; Hodak, E.; Levi, A.
Summary: Background: Solar urticaria (SU) is a rare photodermatosis causing a significant impact on patients' quality of life (QoL), and treatment is often challenging. Aim: To analyse clinical experience with a tailored stepwise therapeutic approach. Methods: A retrospective cohort design was used. Patients with suspected SU underwent laboratory investigations and photoprovocation. Those with a high minimal urticaria dose (MUD) were treated with a single antihistamine (protocol 1), and those with a lower MUD received three types of antihistamines (protocol 2); both protocols included a leucotriene receptor antagonist (LRA). In cases of failure, treatment was switched to omalizumab at doses of < 300 mg/month with incremental dosage increases as necessary (monthly dose range, 150–600 mg/month). Symptom relief and photoprovocation under treatment were evaluated. Results: In total, 30 patients (10 men, 20 women) were enrolled. Most (87%) were sensitive to visible light (1–70 J/cm 2 ) with or without extension to ultraviolet A. Of the 30 patients, 23 opted for our stepwise approach: 22 achieved complete remission on protocols 1 or 2 ( n = 17) or after switching to omalizumab ( n = 5), and another patient achieved partial remission under omalizumab. There were no treatment‐related severe adverse effects. Conclusions: Symptoms of SU can be well controlled by treatment with antihistamines and an LRA tailored to the degree of photosensitivity, followed by omalizumab in refractory cases. This has important implications for patient QoL.